Three decades of continuous wrist‐activity recording: analysis of sleep duration. (17th January 2017) - Borbély, Alexander A.; Rusterholz, Thomas; Achermann, Peter
Summary: Motor activity recording by a wrist‐worn device is a common method to monitor the rest–activity cycle. The first author wore an actimeter continuously for more than three decades, starting in 1982 at the age of 43.5 years. Until November 2006 analysis was performed on a 15‐min time base, and subsequently on a 2‐min time base. The timing of night‐time sleep was determined from the cessation and re‐occurrence of daytime‐level activity. Sleep duration declined from an initial 6.8 to 6 h in 2004. The declining trend was reversed upon retirement, whereas the variance of sleep duration declined throughout the recording period. Before retirement, a dominant 7‐day rhythm of sleep duration as well as an annual periodicity was revealed by spectral analysis. These variations were attenuated or vanished during the years after retirement. We demonstrate the feasibility of continuous long‐term motor activity recordings to study age‐related variations of the rest–activity cycle. Here we show that the embeddedness in a professional environment imparts a temporal structure to sleep duration.